Control and elimination of Schistosoma mansoni infection in adult individuals on Ukerewe island, northwestern Tanzania: baseline results before implementation of intervention measures - Humphrey D. Mazigo; Crecencia Edward Chiombola; Stella Mugassa; Magreth Magambo; Godfrey M. Kaatano; Titus Leeyio; Erick Simon Mwangoka; Tumaini Baumba; Saskia Kreibich; Christa Kasang; Antje Fuss; Andreas Mueller (BMC Infectious Diseases, 2024)
Abstract Background Communities living along the shoreline and on the islands of Lake Victoria in northwestern Tanzania remain endemic for schistosomiasis and suffer from the life-threatening morbidities associated with the disease. Nevertheless, the control measures particularly the mass drug administration do not cover the adult population. The current project on Ukerewe island aims to close this gap by involving adult community members in the control program. Here we report the baseline results of S. mansoni infection and associated hepatosplenic morbidities and factors before implementing the project activities. Methods A cross-sectional analytical study was conducted with 4,043 participants aged ≥ 18 years living in 20 villages on Ukerewe island, northwestern Tanzania. Individual stool and urine samples were collected and examined using the Kato-Katz (KK) technique and point-of-care circulating cathodic antigen testing(POC-CCA) to identify S. mansoni eggs and antigens, respectively. All study participants underwent ultrasound evaluation of S. mansoni hepatosplenic morbidities using the Niamey protocol. Rapid diagnostic tests were used to diagnose HIV infection, hepatitis C and chronic hepatitis B. A questionnaire was used to collect demographic data and reported clinical symptoms of study participants. Results A total of 4,043 participants took part in the study, of which 49.7% (n = 2,009) and 50.3% (n = 2,035) were male and female, respectively. The overall prevalence of S. mansoni infection was 30.4% (95%CI:29.0-31.9%) and 84.7% (95%CI:83.3–85.9%), respectively, based on the KK technique and the POC-CCA test. The geometrical mean eggs per gram of faeces (GMepg) was 105.3 (95%CI:98.7-112.3% GMepg) with 53.9%, 32.4% and 13.7% of the participants having mild, had moderate and severe intensity of infection. The prevalence of hepatitis C, HIV, and hepatitis B was 0.4%, 2.2% and 4.7%, with 0.2%, 2.2% and 5.4% of the infected individuals coexisting with S. mansoni infection. The prevalence of splenomegaly, periportal fibrosis, hepatomegaly, and portal vein dilatation was 40.5%(95%CI: 38.8–42.1%), 48.1%(95%CI:64.4–49.7%), 66.2%(95%CI:4.6–67.7%) and 67.7%(95%CI:66.2–69.2%), with their prevalence varying depending on the demographic information and infection status of the participants. Other detectable ultrasound-related morbidities included ascites (1.7%), collateral veins (18.3%) and gall bladder wall thickness (40.4%). Age groups, gender, reported clinical characteristics, reported non-use of the drug praziquantel, liver imaging pattern, and place of residence remained independently associated with hepatosplenic morbidities. Conclusion The current study setting is endemic for S. mansoni infection and the population has a high prevalence of the disease associated hepatosplenic morbidities characterized by hepatomegaly, splenomegaly, ascites, gall bladder wall thickening, periportal fibrosis and portal vein dilatation. Several demographic, clinical and epidemiological circumstances remained independently associated with S. mansoni infection and associated morbidities. These findings call for integrative intervention efforts, starting with whole community MDA that includes all out of schools community members.